الرقابة الشريعة في المؤسسات المالية الإسلامية :‏ ‏أنموذج فرع بيت التمويل الكويتي بماليزيا، وبنك إسلام الماليزي (دراسة مقارنة) /‏ - Idris, Mahmoud Mohamed Ali Mahmoud (Ma'had al-Masrifiyah wa-al-Maliyah al-Islamiyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study investigates the role of Shariah Advisory Council in Islamic financial institutions, focusing on two cases, namely the Kuwait Finance House branch in Malaysia and Bank Islam Malaysia Berhad. A comparative critical analytical study has been conducted on the activities of these two banks. The study has also examined the achievements and development of the Islamic financial products in Malaysia, which have given Islamic banks the competitive edge in the financial industry. Furthermore, the study has investigated comparatively the performances of the two banks, their instruments and some of the modes of transactions they use, highlighting the views of contemporary scholars and Shari'ah rulings on these instruments. Some of these views necessitate a review of some of these applications to make them Shari'ah compliant. Accordingly, the study has pointed out that in spite of the shortcomings in some of these applications, this does not in any way undermine the abilities of the two banks and the efforts of the scholars offering Shariah Advisory in these two banks. The study has adopted a comparative operational method to examine the two banks and their products profoundly. The study concludes that the experiences of the Kuwait Finance House branch and Bank Islam Malaysia Berhad, despite some of the shortcomings, are generally successful and can be good examples for overcoming the present global financial crisis.